THE IMPLEMENTATION OF ONLINE LEARNING POLICY DURING THE COVID-19 PANDEMIC AT DHARMAWANGSA UNIVERSITY - Amini Amini; Ainun Mardhiah; Akrim Akrim (UIN Sumatera Utara Medan, 2021)
This study aims to determine (1) to describe the online learning policy at Dharmawangsa University, (2) Describe and analyze the Implementation of Online Learning Policies During the COVID-19 Pandemic Period at Dharmawangsa University., (3) Describe whether there are any obstacles during the online learning process (4) Describe what inputs can be taken from student complaints about the online learning process at Dharmawangsa University. Data collection techniques in research using interview techniques and documentation. The data analysis technique used in this research is qualitative analysis through data reduction, data display, and conclusion drawing. The results of this study indicate that (1) Dharmawangsasudang University followed the instructions of the Ministry of Education and Culture SE No. 5 of 2020 and SE of Higher Education No. 1 of 2020 and was following these instructions. (2) Lecturers and teaching staff at Dharmawangasa University also know the Circular. However, it is not comprehensive (3) The implementation of online learning policies during the COVID-19 pandemic at Dharmawangsa University, most of the lecturers answered less effectively, especially when taking lessons where the courses required doing practicum or practice so that they could not run under learning outcomes. (4 ) There are significant obstacles when the online learning process is carried out, including uneven network connections in the student's residential area and insufficient internet quota in carrying out the online learning. (5) As for input from complaints submitted by students during the learning policy online during the pandemic, including uneven network connections and the lack of quotas owned by students.